Glycemic Status and In-hospital Complications in Acute Ischemic Stroke - Hossain, Md Amir; Hannan, MA; Barua, Ripon; Hossain, Mohammed Shahadat; Ahmed, Sharif Uddin; Sina, Hashmi; Jahan, Merina (Journal of Shaheed Suhrawardy Medical College, 2018)
Although on-admission high glycemic status in acute ischemic stroke (AIS) patients is associated with poor in-hospital outcome, the impact of on-admission different glycemic status in AIS is less clear. This prognostic cohort study was aimed to evaluate the association of on-admission high glycemic status with in-hospital complications of AIS patients. This study was conducted by measurement of random blood glucose (RBG) in 90 AIS patients within 24 hours of hospitalization. The patients were divided into three groups based on their RBG in mg/dl: Group A <120, Group B 120-180 and Group C >180. The average age was 59 years and 35.6% patients were diabetic. In AIS patients, higher RBG was associated with increased in-hospital complications regardless of a history of diabetes mellitus (p=0.047, 0.040, 0.003 and 0.015 for urinary tract infection, bed sore, electrolyte imbalance and mixed complications respectively). Optimal glucose targets in hospitalized patients with AIS are currently undetermined. Glycemic and nonglycemic interventions should be studied for their impact on in-hospital complications and cost. J Shaheed Suhrawardy Med Coll, December 2016, Vol.8(2); 44-48